2013
DOI: 10.3126/jcmsn.v8i3.8678
|View full text |Cite
|
Sign up to set email alerts
|

Microbial infection and antibiotic patterns among intensive care unit patients in a tertiary hospital in Central Nepal

Abstract: AimsThe present study is a fundamental effort to evaluate the bacteriological and antibiotic patterns in the Intensive Care Unit (ICU) setting in a tertiary care hospital. This study was carried out to guide the clinician in choosing the appropriate antibiotics and to prevent emergence of multidrug resistance bacteria. Materials and MethodsBetween March 2009 to Feb 2012, the samples from various ICUs that were submitted to the microbiology laboratory for culture and sensitivity were included in this study. All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 14 publications
3
6
0
Order By: Relevance
“…while in other studies percentage varied from 28% to 67%. [1][2][3][4][5][6][7] This difference may be due to This study showed that gram-negative infection is more common than gram-positive which is similar to other studies from developing country whereas gram-positive infection is more common in developed country. [1][2][3][4][5][6][7][8] The present study shows that tracheal aspirate 49(36.26%) was a common sample which is similar to other studies.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…while in other studies percentage varied from 28% to 67%. [1][2][3][4][5][6][7] This difference may be due to This study showed that gram-negative infection is more common than gram-positive which is similar to other studies from developing country whereas gram-positive infection is more common in developed country. [1][2][3][4][5][6][7][8] The present study shows that tracheal aspirate 49(36.26%) was a common sample which is similar to other studies.…”
Section: Discussionsupporting
confidence: 72%
“…[1][2][3][4][5][6][7] This difference may be due to This study showed that gram-negative infection is more common than gram-positive which is similar to other studies from developing country whereas gram-positive infection is more common in developed country. [1][2][3][4][5][6][7][8] The present study shows that tracheal aspirate 49(36.26%) was a common sample which is similar to other studies. 1,3,7,9 Studies conducted by Raval et al 10 and Sarkar et al 11 have shown that urinary tract infection was more common than respiratory tract infection.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Findings of our study are similar to studies from Nepal and India. 18,20 Pseudomonas aeruginosa, Klebsiella species, E coli, S. aureus and Enterococcus species are the most frequent pathogens reported from ICUs of different hospitals of Asian countries. 16,18,19 In this study, Acinetobacter was the most common pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…37 Many studies from ICUs have reported isolation of similar organisms. 16,20 Infections caused by ESKAPE group organisms especially among ICU patients are difficult to treat and have high morbidity and mortality. 38…”
Section: Discussionmentioning
confidence: 99%